Enhancing the performance of V Rossi wheels for motorcycles through finite element analysis using Solidworks - Fathony Arifin; Farid R. Vafazov (Innovation in Engineering, 2024)
Enhancing motorcycle wheel performance has significant implications for rider stability, maneuverability, and comfort. In this context, finite element analysis has emerged as a crucial method for understanding and enhancing wheel performance. This study aims to delve into the potential of utilizing Solidworks to elevate the performance of V Rossi motorcycle wheels. By blending contemporary engineering principles with advanced simulation technology, the research presents a structural analysis and response of V Rossi wheels to various load conditions. Through innovative design and the integration of Solidworks Simulation, the study seeks to provide profound insights into the motorcycle industry. Solidworks proficiently calculates strain and stress on motorcycle wheel rims, facilitating numeric computation and streamlined design processes. Additionally, Solidworks adeptly handles scaling and meshing while accurately determining the strain and stress required for the wheel rims. The V Rossi wheels are ideally suited for contemporary usage with the ever-evolving modern landscape and the current millennial era.